Beyond climate envelope projections: Roe deer survival and environmental change. Issue 3 (8th January 2016) - Davis, Miranda L.; Stephens, Philip A.; Kjellander, Petter
ABSTRACT: Research on climate change impacts has focused on projecting changes in the geographic ranges of species, with less emphasis on the vital rates giving rise to species distributions. Managing ungulate populations under future climate change will require an understanding of how their vital rates are affected by direct climatic effects and the indirect climatic and non‐climatic effects that are often overlooked by climate impact studies. We used generalized linear models and capture–mark–recapture models to assess the influence of a variety of direct climatic, indirect climatic, and non‐climatic predictors on the survival of roe deer ( Capreolus capreolus ) at 2 sites in Sweden. The models indicated that although direct climatic effects (e.g., precipitation) explained some variation in survival, indirect climatic effects (e.g., an index of vegetation production), and non‐climatic effects (hunting by lynx [ Lynx lynx ] and humans) had greater explanatory power. Climate change is likely to increase vegetation productivity in northern Europe, and, coupled with the positive effects of vegetation productivity on roe deer survival, might lead to population increases in the future. Survival was negatively affected by lynx presence where these predators occur and by human harvest in the site that lacked predators. In the future, managers might find that a combination of increased harvest and predation by recovering carnivore populations may be necessary to mitigate climate‐induced increases in roe deer survival. Considering vegetation availability and predation effects is likely to improve predictions of ungulate population responses to variation in climate and, therefore, inform management under future climate change. © 2016 The Wildlife Society.